Difficult questions of intravenous thrombolytic therapy in ischemic stroke - Aleksey A. Kulesh (ZAO "Consilium Medicum", 2021)
The article reflects the current achievements in the field of reperfusion therapy for ischemic stroke. The data are presented that allow a practicing neurologist to make informed decisions about intravenous thrombolysis in difficult clinical situations: minor stroke, suspected stroke "mask", atypical clinical picture, patient's age over 80 years, posterior circulation stroke, isolated dizziness, severe neurological deficit, large artery occlusion, chronic neuroimaging changes, polymorbidity and low functional level before stroke. It has been shown that an increase in the number of candidates for intravenous thrombolysis can be achieved by intensifying the selection of patients within the 4.5-hour therapeutic window, which primarily implies the optimization of local stroke treatment protocols with a reduction in the door-to-needle time, as well as, in the short term, expanding the therapeutic window. Approaches to reduce the risk of symptomatic hemorrhagic transformation are discussed. We are also talking about a rare but life-threatening complication angioedema. Thus, the intensification of intravenous thrombolysis, as well as an increase in its effectiveness and safety are the primary tasks of each stroke department.